The Role of the International Judiciary in Protecting the Holy Places - Naser Abdulridha, Jaafar; Jaber Hashim, Salwan; Ressan Gadder, Ghani (International Journal of Criminology and Sociology, 2022)
The protection of the sacred places that constitute the spiritual values of peoples is no less important than the protection of the physical entity of man, because of the attachment of these sanctities as a cultural and civilized entity. There is no doubt that the continuous and significant increase in the violation of the holy sites calls for the need to consider the legal protection of these holy places as an urgent necessity to preserve them. Attacks on holy sites represent a real threat to international peace and security, through the effects of the encroachment or threat to these holy sites, which leads to significant damage caused by armed conflicts, whether internal, regional or international. The legal basis for the protection of the holy places is closely linked to the development of the civilized thought of the international community. What is being reported today in the international community about violence and its escalation is related to the violation of the sacred places that affect the conscience and conscience at its core. The international community should therefore recognize that the more it plays its part properly, the sooner these violations will be put in place the less likely there will be an escalation of violence.